Licenciatura em Geografia na Unioeste - Campus de Marechal Cândido Rondon-PR: história do curso de Formação de Professores e destino dos egressos entre 2000 a 2018 - Barbosa, Rosângela Aparecida Jacoby (2022)
The beginning of the process of training Geography teachers in Brazil arises in the context of the creation of the Faculties of Philosophy, Letters and Human Sciences (FFLCH - USP) in the country, in 1934. However, the legislation in force in each period points to changes in the demand for graduates in the discipline, expanding the search for higher education. Based on this demand, in 1997, the Degree in Geography at the State University of West Paraná, Campus de Marechal Cândido Rondon, to meet the need of schools for professionals trained in this discipline. Thus, in the period after of the LDB 939/94, the licentiate courses involved with the initial training of teachers strive to train critical teachers, capable of developing their profession autonomously in the future for all levels of education, with greater demand in basic education. In this context, as the objective presents research, sought to characterize the situation of graduates from the application of questionnaires to collect data related to information such as: gender, performance or in the basic education network in the area of Geography, conclusion of the course, if located or not in the municipality of training, where they are currently, what level of training did the respondents reach. In order to understand the importance of the university in the training process, the history of the implementation of the Geography Course at UNIOESTE, Campus de Marechal Cândido Rondon, was rescued from documents and interviews with professors directly involved in this implementation. There were eight university professors for knowledge of facts about the creation of the course of courses that took place throughout its existence. The interviews were carried out by the Google Meet Platform and by written contributions, via email. About the graduates, taking into account that Unioeste has been training teachers in the area of Geography for more than two decades and due to the current conditions of teaching, we sought to analyze whether these graduates are, in fact, exercising the profession as teachers of the discipline in basic education. The main methodological resource of this research was the application of a questionnaire sent to graduates of the period of interest via the Internet, through the Google Forms system. Among the graduates located, 176 graduates responded, and nine were also interviewed in order to complement some information. The questionnaire was distributed only to graduates who completed the degree in Geography at Unioeste in Marechal Cândido Rondon until the year 2018. As a result, the study allows us to identify how many graduates, among the respondents, are working in the education area, as Geography teachers or in other areas, where they are currently and what is the university's participation in the formation of the geography teachers in question.